2019
DOI: 10.3390/molecules24244550
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Compounds in Fruit Peels as Novel Biomarkers for the Identification of Four Citrus Species

Abstract: The aroma quality of citrus fruit is determined by volatile compounds, which bring about different notes to allow discrimination among different citrus species. However, the volatiles with various aromatic traits specific to different citrus species have not been identified. In this study, volatile profiles in the fruit peels of four citrus species collected from our previous studies were subjected to various analyses to mine volatile biomarkers. Principal component analysis results indicated that different ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 31 publications
2
19
0
Order By: Relevance
“…The chemical components identified in the peels of 66 citrus germplasms from four Citrus horticultural groups (mandarin, orange, grapefruit, and lemon) were also used for biomarker mining. Thirty potential biomarkers were identified, and four compounds (β-elemene, valencene, nootkatone, and limettin) were validated as biomarkers [29]. However, Luro et al [30] found that the diversity based on leaf oil compositions from Citrus medica varieties did not agree with the molecular diversity and was therefore unsuitable for intraspecific phylogenetic studies.…”
Section: Introductionmentioning
confidence: 99%
“…The chemical components identified in the peels of 66 citrus germplasms from four Citrus horticultural groups (mandarin, orange, grapefruit, and lemon) were also used for biomarker mining. Thirty potential biomarkers were identified, and four compounds (β-elemene, valencene, nootkatone, and limettin) were validated as biomarkers [29]. However, Luro et al [30] found that the diversity based on leaf oil compositions from Citrus medica varieties did not agree with the molecular diversity and was therefore unsuitable for intraspecific phylogenetic studies.…”
Section: Introductionmentioning
confidence: 99%
“…The increases in terpene hydrocarbons at OD-50 °C might have been caused by the release of bound volatiles (enzymatic or acid hydrolysis) during the drying process, since volatiles exist in free forms or bound to other molecules such as sugars forming glycosides [ 73 ]. Nevertheless, the oven-drying at 70 °C caused a significant decrease ( p < 0.05) in the global levels terpene hydrocarbons ( Figure 1 ) since drying at medium-high temperatures can cause stripping processes, oxidation, and thermal degradation reactions [ 74 ]. In particular, limonene at OD-70 °C decreased to 1000 µg/g in samples dried at 70 °C, even to 852.33 µg/g in Salustriana peels.…”
Section: Resultsmentioning
confidence: 99%
“…β-caryophyllene, γ-cadinene, and (+)-δ-cadinene were also critical for the separation of those groups ( Figure 8 E). Regarding their relative abundance, these compounds have been identified as chemical markers in other plant species such as Salvia runcinata [ 57 ], Leonotis leonurus [ 58 ], peels of citrus fruits [ 59 ], Lantana radula and L. canescens [ 60 ]. In the same context, 1, 8-cineole and β-caryophyllene were tagged as chemical markers and used to differentiate chemotypes for the essential oil of Thymus serpyllum [ 61 ].…”
Section: Discussionmentioning
confidence: 99%